Culture-specific terms as verbal expressive peculiar features of national cultures - Yerbulatova, K.; Mugtasimova, G. R.; Kirillova, Z. N.; Sahin, L. (Astra Salvensi. - 2017, 2017)
The issues concerning the translation have become more topical, since foreign literature remains one of the main, and perhaps the primary source of knowledge about other cultures. The practice of translating fictional texts proves the complexity of conveying national specifics and reveals the need for a more detailed study of this phenomenon. The mastery of an interpreter is not only in the ability to reveal the units of translation with a national-cultural component of meaning, but also in an understanding of what to preserve in translationand how. In the process of studying and interacting languages, the problem of understanding and translating culture-specific terms is always relevant.In every language there are the words and phrases, the so-called culture-bound terms that express the concepts of a certain culture and are absent in other languages, which can cause difficulties or misunderstandings in intercultural communication. This article deals with the issues of studying and translating the units with a national-cultural element of meaning. The proposed material reflects the national and cultural specifics of real things, shows their connection with historical events, changes in public life. The questions of equivalent translation of culturebound termsare discussed. The authors show the dependence of the choice of translation strategy on external socio-cultural and pragmatic factors. Вопросы перевода стали более актуальными, поскольку зарубежная литература остается одним из основных, а может быть, и основным источником знаний о других культурах. Практика перевода художественных текстов доказывает сложность передачи национальной специфики и выявляет необходимость более детального изучения этого явления. Мастерство переводчика заключается не только в умении раскрывать единицы перевода с национально-культурной составляющей значения, но и в понимании того, что и как сохранять в переводе. В процессе изучения языков и взаимодействия с ними всегда актуальна проблема понимания и перевода терминов, связанных с определенной культурой. В каждом языке есть слова и фразы, так называемые термины, связанные с культурой, которые выражают концепции определенной культуры и отсутствуют на других языках, что может вызвать трудности или недопонимание в межкультурном общении. В данной статье рассматриваются вопросы изучения и перевода единиц с национально-культурным элементом значения. Предлагаемый материал отражает национально-культурную специфику реальных вещей, показывает их связь с историческими событиями, изменениями в общественной жизни. Обсуждаются вопросы эквивалентного перевода терминов, связанных с культурой. Авторы показывают зависимость выбора переводческой стратегии от внешних социокультурных и прагматических факторов.
Keywords: импакт-фактор 2017; скопус; зарубежные авторы; дальнее зарубежье; научный журнал; языкознание; термины